Prior knowledge biases the visual memory of body postures - Qiu Han; Marco Gandolfo; Marius V. Peelen (iScience, 2024)
Summary: Body postures provide information about others’ actions, intentions, and emotions. Little is known about how postures are represented in the visual system. Considering our extensive visual and motor experience with body postures, we hypothesized that priors derived from this experience may systematically bias visual body posture representations. We examined two priors: gravity and biomechanical constraints. Gravity pushes body parts downward, while biomechanical constraints limit the range of possible postures (e.g., an arm raised far behind the head cannot go down further). Across three experiments (N = 246), we probed participants’ visual memory of briefly presented postures using change discrimination and adjustment tasks. Results showed that lifted arms were misremembered as lower and as more similar to the nearest biomechanically plausible postures. Inverting the body stimuli eliminated both biases, ruling out visual confounds. These findings show that visual memory representations of body postures are modulated by a combination of category-general and category-specific priors.